(3GdehGRfI GdYGeI hHfjI GdfGJL GdeMdj GdELeGdj s - (3egOj SgQ ZjdGf(B, (3GdLHhQjs ((3YeGf(B:s (3OGQ GdCjGe ddfTQ hGdJhRjY(B,s, 2018)
(3jYGdL gPG GdcJGH ehVhY GdehGRfI GdYGeI hHfjI GdfGJL GdeMdj GdGLeGdj, hjbSe gjcd GdcJGH Edi KdGKI aUhd ,EPG JfGhd GdaUd GdChd GdGWGQ GdeaGgjej ddehGRfI GdYGeI hHfjI GdfGJL, hjJVef GdaUd KdGKI eHGMK, GdeHMK GdChd JfGhd GdEWGQ GdeaGgjej ddehGRfI GdYGeI hGdKGfj JfGhd GdGWGQ GdfXQj dHfjI GdfGJL hGdKGdK JfGhd GdEWGQ GdeaGgjej ddGNJdGdGJ GdgjcdjI(B. (3GdaUd GdKGfj JfGhd GdGWGQ GdJMdjdj ddYdGbI Hjf GdehGRfI GdYGeI hHfjI GdfGJL aj GdYQGb, hJVef GdaUd eHMKjf , GdeHMK GdGhd JMdjd GdehGRfI GdYGeI aj GdGbJUGO GdYQGbj NdGd eOI GdOQGSI , hGdKGfj JfGhd JMdjd HfjI GdfGJL aj GdGbJUGO GdYQGbj NdGd eOI GdOQGSI (B. (3GdaUd GdKGdK JfGhd bjGS hJMdjd GdYdGbI Hjf GdehGRfI GdYGeI hHfjI GdfGJL aj GdYQGb, hJVef GdaUd eHMKjf GdChd JfGhd GdCSGdjH GdbjGSjI GdeSJNOeI aj GdJMdjd , hGdKGfj JMdjd GdfJGFL(B.s
(3HHdjhZQGajG U(B.253s
Keywords: (3GdGbJUGOs; (3GdehGRfI GdYGeIs; (3GdfGJL GdeMdjs